Association between upper and lower respiratory disease among patients with primary ciliary dyskinesia: an international study. - GÖKDEMİR, YASEMİN (My University, 2024)
Introduction: Nearly all patients with primary ciliary dyskinesia (PCD) report ear-nose-throat (ENT) symptoms. However, scarce evidence exists about how ENT symptoms relate to pulmonary disease in PCD. We explored possible associations between upper and lower respiratory disease among patients with PCD in a multicentre study. Methods: We included patients from the ENT Prospective International Cohort (EPIC-PCD). We studied associations of several reported ENT symptoms and chronic rhinosinusitis (CRS)—defined using patient-reported information and examination findings—with reported sputum production and shortness of breath—using ordinal logistic regression. In a subgroup with available lung function results, we used linear regression to study associations of CRS and FEV1, accounting for relevant factors. Results: We included 457 patients [median age: 15; interquartile range (IQR) 10–24; 54% males]. Shortness of breath associated with reported nasal symptoms and ear pain of any frequency, often or daily hearing problems, headache when bending down [odds ratio (OR) 2.1; 95% confidence interval (CI) 1.29–3.54], and CRS (OR 2.3; 95% CI 1.57–3.38) regardless of polyp presence. Sputum production associated with daily reported nasal (OR 2.2; 95% CI 1.20–4.09) and hearing (OR 2.0; 95% CI 1.10–3.64) problems and CRS (OR 2.1; 95% CI 1.48–3.07). We did not find any association between CRS and FEV1. Conclusion: Reported upper airway symptoms and signs of CRS associated with reported pulmonary symptoms; however, not with lung function. Our results emphasise assessing and managing upper and lower respiratory disease as a common, interdependent entity among patients with PCD.
Keywords: Primary ciliary dyskinesia; epidemiology; orphan disease; upper airways; lung function